2004
DOI: 10.1001/archsurg.139.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Fine-needle Aspiration Cytologic Examination on Clinical Outcome in Patients With Hepatocellular Carcinoma in a Tertiary Referral Center

Abstract: Hypothesis: Preoperative fine-needle aspiration cytologic examination (FNAC) exerts a statistically significant adverse effect on long-term clinical outcome in patients with hepatocellular carcinoma (HCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…57 For lesions 10 to 20 mm 32 or > 10 to 20 mm. 27 in size, the sensitivity ranged from 65% to 96% for CT and from 89% to 92% for MRI. For liver transplantation, it is especially important that the diagnosis of HCC be correct for lesions > 20 mm because these patients receive additional MELD points to expedite transplantation in many countries.…”
Section: Level 1b Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…57 For lesions 10 to 20 mm 32 or > 10 to 20 mm. 27 in size, the sensitivity ranged from 65% to 96% for CT and from 89% to 92% for MRI. For liver transplantation, it is especially important that the diagnosis of HCC be correct for lesions > 20 mm because these patients receive additional MELD points to expedite transplantation in many countries.…”
Section: Level 1b Studiesmentioning
confidence: 98%
“…12,13,17,[20][21][22][23][24] We identified 4 more studies. [25][26][27][28] Three of these studies were not analyzed because the reference standard was poorly defined 27,28 or some of the patients were not followed up. 25 In all, we included 1 systematic review and 9 single studies in the analysis (Tables 3 and 4).…”
Section: Question 2 What Are the Complications Of Tumor Biopsy?mentioning
confidence: 99%
“…The interval between detected seeding and biopsy varies from several months to 3 years. Whilst some studies have shown that preoperative FNA has no statistically adverse effect on the operability, possibility of tumor spread, or long-term survival of HCC patients [38, 39], there are others which strongly maintain that pretransplant FNA diagnosis of HCC is not necessary [40, 41]. Seeding is usually noted with subcapsular tumors and those of high-grade malignancy; these tend to be tumors >2 cm.…”
Section: Fine Needle Aspiration Biopsy From the Point Of View Of Tmentioning
confidence: 99%
“…[15][16][17][18][19] Other investigators have not observed an increased risk of tumor spread. [20][21][22] Cases should be considered individually and biopsy may prove useful in cases in which imaging is not diagnostic or even in cases of large liver tumors that would be considered for transplant if the tumor grade was well differentiated. 23 In addition, concerns over sampling bias still remain.…”
Section: When To Obtain a Liver Biopsy To Diagnose Hepatocellular Carmentioning
confidence: 99%